Tiessa (Pouteria campechiana) as an indigenous ripening agent for mangoes var. carabao - Camot, Mary Jane Calantuan
Three methods using tiessa (Pouteria campechiana) as an indigenous ripening agent were done as treatment on carabao mangoes.